Cover Feature: Isomerization and Dimerization of Indocyanine Green and a Related Heptamethine Dye (Eur. J. Org. Chem. 30/2019). Issue 30 (8th August 2019) - Rüttger, Franziska; Mindt, Sonani; Golz, Christopher; Alcarazo, Manuel; John, Michael
Abstract : The Cover Feature shows the dimer of Indocyanine Green (ICG), a dye that is currently widely employed in the diagnostics of hepatitic function, angiography, and tumor imaging and surgery. The highly specific formation of the central C–C bond between the two ICG heptamethine chains requires both light (ICG absorption maximum ≈ 800 nm) and molecular oxygen. Furthermore, ICG undergoes trans ‐ cis photoisomerization of its heptamethine chain, and these isomers are also detected by low‐temperature NMR spectroscopy. More information can be found in theCommunication by M. John et al.